Savings and investment correlations in response to monetary policy shocks: New insights into the Feldstein-Horioka puzzle? - Caroline Schmidt (ETH Zurich, KOF Swiss Economic Institute, 2006)
In this paper, it is argued that the observed high positive correlation between national savings and investment which is found in the data can in part be explained by shocks to monetary policy. This hypothesis, which is established by reviewing some empirical findings, is tested in a two-country DSGE-model framework in the tradition of the New Open Economy Macroeconomics. The simulation results obtained support the idea that shocks to monetary policy might contribute to the explanation of the Feldstein-Horioka puzzle.
Keywords: E2; E52; F32; 330; Savings Investment Correlations; Monetary Policy Shocks; Feldstein-Horioka Puzzle; Local-currency pricing; Sparen; Investition; Korrelation; Geldpolitik; Schock; Theorie